Dynamic monitoring of antibody drug conjugates targeting TROP2 or HER2 in breast cancer using circulating tumor cells - Avanish Mishra; Rachel O. Abelman; Quinn Cunneely; Victor Putaturo; Akansha A. Deshpande; Remy Bell; Elizabeth M. Seider; Katherine H. Xu; Mythreayi Shan; Justin Kelly; Shih-Bo Huang; Olivia Rieur; et al. (Proceedings of the National Academy of Sciences, 2026)
Antibody–drug conjugates (ADCs) target surface proteins on cancer cells, leading to internalization and delivery of a drug payload, thereby enhancing selectivity and minimizing toxicity. ADCs against TROP2 (Sacituzumab govitecan) or HER2 (T-DXd) have demonstrated efficacy in metastatic breast cancer, yet paradoxically, outside of HER2 -amplified breast cancers, expression levels of these breast cancer-enriched epitopes in tumor biopsies have not been strongly correlated with clinical response. We undertook serial quantitative imaging of circulating tumor cells (CTCs) in a prospective cohort of 35 patients treated with either of these ADCs. At the single-cell level, expression of TROP2 and HER2 within individual patients is highly heterogeneous in both CTCs and paired tumor biopsies. Measurement of these epitopes on CTCs immediately prior to ADC therapy does not predict depth of clinical response. However, absence of CTCs or >80% reduction in CTC numbers after three weeks of treatment (CTC Low ) predicts durable response, compared with CTC High cases (TROP2: HR 5.15, P = 0.012; HER2: HR 6.01, P < 0.001). Targeted epitopes are not commonly downregulated on CTCs at the time of acquired clinical resistance, and switching between TROP2- and HER2-targeting ADCs sharing similar payloads infrequently leads to second-line response. Thus, while CTC burden is correlated with response to these ADCs, the level of TROP2 or HER2 expression is poorly predictive. These findings point to sensitivity to the drug payload as a potential driver of clinical response to currently approved ADCs in breast cancer.